Makna Toponim Desa Durungbedug Sebeagi Representasi Warisan Budaya Lokal - Andi Fikri; Istiqomah Istiqomah; Arifin Mado (BRILIANT: Jurnal Riset dan Konseptual, 2026)
This study aims to examine the meaning of toponyms in Durungbedug Village as a representation of local cultural heritage. Using a comparative historical linguistics approach, Barthes' etymology and semiotics, as well as ethnographic methods, this study explores the meaning of place names in the village. Scientific findings indicate that the toponyms of Durungbedug Village, consisting of Bedug Pesantren, Bedug Dowo, and Bedug Baru, reflect the existence of developing religious, agrarian, and economic values. "Bedug Pesantren" reflects religious traditions, "Bedug Dowo" indicates still-perpetuated agrarian practices, while "Bedug Baru" depicts economic dynamics that keep pace with the times. The contribution of this study is to provide a new understanding that toponyms are not only geographical markers, but also reflect social, cultural, and economic changes, as well as enriching the study of local cultural heritage.